Acceptability of novel antioxidant ice cream fortified - Siti Radhiah Omar (2024)
This research aimed to determine the total antioxidant activity and total phenolic content of the papaya seeds. These papaya seeds then were introduced into the prepared ice cream to determine the effect of the papaya seeds to the physicochemical and the acceptability of ice cream by making four different formulations (Control, 1.0%, 2.0%, and 3.0% of papaya seeds). Two methods namely free radical scavenging assay (DPPH) and ferric reducing antioxidant power (FRAP) were used to determine the total antioxidant activity of the papaya seeds, whereas total phenolic content was determined by FolinCiocalteu’s method (TPC). The papaya seeds showed high total phenolic content in the TPC analysis result. Furthermore, DPPH and FRAP showed high antioxidant activity of the papaya seeds. Acceptability of the ice cream was conducted by sensory evaluation and the results showed that the control (0.0%) papaya seeds ice cream formulation was the most favorable by the panelists followed by 1.0%, 2.0%, and 3.0% papaya seeds formulation. In conclusion, the papaya seeds are proven to contain antioxidants by the results given in DPPH, FRAP, and TPC tests. Surprisingly, the papaya seeds also did not affect the physicochemical of the ice cream and the ice cream was accepted by the panelists.